Demineralization and hydrogen peroxide penetration in teeth with incipient lesions - Briso, André Luiz Fraga [UNESP]; Gonçalves, Rafael Simões [UNESP]; Costa, Fernanda Bernardi da [UNESP]; Gallinari, Marjorie de Oliveira [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Santos, Paulo Henrique dos [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the demineralization and hydrogen peroxide (HP) penetration in teeth with incipient lesions submitted to bleaching treatment. For analysis of HP penetration, sound and demineralized enamel/dentin discs were placed in artificial pulp chambers containing acetate buffer solution. After bleaching treatment, this solution was subjected for analysis of optical density by spectrophotometry and the disc surfaces were analyzed with scanning electron microscopy (SEM) and polarized light microscopy (PLM). The remaining discs were subjected for cross-sectional hardness analysis at different depths. Data were analyzed by repeated measures ANOVA and PLSD Fisher test (a=0.05). It was observed that previously demineralized teeth showed greater HP penetration (p<0.05). The bleaching treatment caused changes to a depth of 20 µm in sound enamel and up to 90 µm in demineralized enamel. SEM and PLM images revealed that the bleaching treatment caused superficial changes that were considerably more accentuated in previously demineralized teeth. It may be concluded that the enamel mineralization level influences HP penetration and the bleaching agent contributed to increase the demineralization depth.

O objetivo deste estudo foi avaliar a desmineralização e a penetração do peróxido de hidrogênio (HP) em dentes com lesões incipientes submetidos ao tratamento clareador. Para analisar a penetração do peróxido de hidrogênio, discos de esmalte/dentina hígidos e desmineralizados foram posicionados em câmaras pulpares artificiais contendo solução tampão de acetato. Após o tratamento clareador, esta solução foi submetida à análise da densidade óptica no espectrofotômetro e as superfícies dos discos foram analisadas por meio de microscopia eletrônica de varredura (MEV) e microscopia de luz polarizada (MLP). Os discos restantes foram submetidos à análise de microdureza transversal em diferentes profundidades. Os dados foram submetidos aos testes ANOVA e teste PLSD Fisher (α= 5%). Observou-se que os dentes previamente desmineralizados mostraram maior penetração de HP (p<0,05). O tratamento clareador causou alterações em uma profundidade de 20 μm em esmalte hígido e até 90 μm em esmalte desmineralizado. As imagens obtidas em PLM e MEV mostraram que o tratamento clareador promove alterações superficiais no esmalte, sendo mais pronunciadas em dentes previamente desmineralizados. Foi concluído que o nível de mineralização do esmalte influencia a penetração do PH e que o agente clareador contribuiu para o aumento da profundidade de desmineralização.
Keywords: Bleaching; Hydrogen peroxide; Tooth demineralization; Caries